2005
DOI: 10.3748/wjg.v11.i36.5621
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of bromocriptine and tumor necrosis factor-α on reversing hepatocellular carcinoma multidrug resistance in nude mouse MDR1 model of liver neoplasm

Abstract: Abstract Abstract Abstract AIM:To investigate the effect of bromocriptine (BCT) and tumor necrosis factor-α (TNF-α) on hepatocellular carcinoma (HCC) multidrug resistance (MDR) in nude mouse MDR model of liver neoplasm. METHODS:Human hepatocarcinoma cell line HepG 2 , drug resistant hepatocarcinoma cell line HepG 2 /adriamycin (ADM) and hepatocarcinoma cell line transfected with TNF-α gene HepG 2 /ADM/TNF were injected into the liver of nude mice via orthotopic implantation and MDR model of liver neoplasm in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Consistent with the pre-clinical findings of cytokine-mediated chemosensitization, clinical trials have demonstrated synergism of combinations of cytostatic drugs with TNF-α or interferones in cancer patients (14,15). Among all cytokines used for ABCB1 expression modulation, TNF-α has shown the highest efficiency in vitro, in vivo and in clinical approaches (9,11,13,16). Although the TNF-α mediated effects on ABCB1 expression were repeatedly shown at functional level, it is still not fully understood, what mechanism in cell signalling is reponsible for these effects.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Consistent with the pre-clinical findings of cytokine-mediated chemosensitization, clinical trials have demonstrated synergism of combinations of cytostatic drugs with TNF-α or interferones in cancer patients (14,15). Among all cytokines used for ABCB1 expression modulation, TNF-α has shown the highest efficiency in vitro, in vivo and in clinical approaches (9,11,13,16). Although the TNF-α mediated effects on ABCB1 expression were repeatedly shown at functional level, it is still not fully understood, what mechanism in cell signalling is reponsible for these effects.…”
Section: Introductionmentioning
confidence: 66%
“…Among these approaches the use of cytokines has shown promise for downregulation of ABCB1 in association with increased drug uptake and chemosensitization of tumor cells (5). Several studies have shown, that cytokines, such as tumor necrosis factor α (TNF-α), interferon γ (IFN-γ), leukoregulin and interleukin-2 (IL-2) are capable of reducing ABCB1 gene expression and increasing chemosensitivity of different cancer cell lines in vitro, and more recently also for endothelial cells in the blood-brain barrier (6)(7)(8)(9)(10)(11)(12). It has been shown, that particularly persistent treatment with these cytokines is of importance to achieve significant reduction in ABCB1 gene expression (6,7,9,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As glutathione is essential for detoxification, the catalytic subunit of glutamate-cysteine ligase (GCLC) was monitored, as well as glutathione-S-transferase (GST). Published primers were chosen for GAPDH, MDR1, MRP1, MRP2, MRP3, GST [30], LRP [8], and GCLC [25]. Primers are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, TNF‐α combined with cytotoxic agents has been proven to enhance the sensitivity to anti‐cancer treatments in many tumours. Combination with bromocriptine and TNF‐α also reversed HCC MDR in a model of liver neoplasm (16).…”
mentioning
confidence: 99%